Cu2O Photocathode for Low Bias Photoelectrochemical Water Splitting Enabled by NiFe-Layered Double Hydroxide Co-Catalyst - Qi, Huan (2017)
Layered double hydroxides (LDHs) are bimetallic hydroxides that currently attract considerable attention as co-catalysts in photoelectrochemical (PEC) systems in view of water splitting under solar light. A wide spectrum of LDHs can be easily prepared on demand by tuning their chemical composition and structural morphology. We describe here the electrochemical growth of NiFe-LDH overlayers on Cu2O electrodes and study their PEC behavior. By using the modified Cu2O/NiFe-LDH electrodes we observe a remarkable seven-fold increase of the photocurrent intensity under an applied voltage as low as −0.2 V vs Ag/AgCl. The origin of such a pronounced effect is the improved electron transfer towards the electrolyte brought by the NiFe-LDH overlayer due to an appropriate energy level alignment. Long-term photostability tests reveal that Cu2O/NiFe-LDH photocathodes show no photocurrent loss after 40 hours of operation under light at −0.2 V vs Ag/AgCl low bias condition. These improved performances make Cu2O/NiFe-LDH a suitable photocathode material for low voltage H2 production. Indeed, after 8 hours of H2 production under −0.2 V vs Ag/AgCl the PEC cell delivers a 78% faradaic efficiency. This unprecedented use of Cu2O/NiFe-LDH as an efficient photocathode opens new perspectives in view of low biasd or self-biased PEC water splitting under sunlight illumination.